Mewujudkan Sistem Peradilan Pidana Berwibawa Di Indonesia - C. Maya Indah S (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The authoritative criminal justice system in Indonesia should be realized in order to get trust and respect from the society. The basic norm order which is embraced in the legal principles is the manifestation of the supreme bases, that is the Grand norm of Pancasila. It should become the legal spirit in the legal validity and reality. The authoritative criminal justice system shall occur when the criminal justice system holds high the criminal legal principles as the meta norm and the attitude guidance. The accountability aspect for criminal justice and its implication towards controllability and responsiveness of institute is very significant in the development of the authoritative justice system. Therefore, it requires a system approach to promote structural, substantial, and cultural synchronizations for the sake of the establishment of legal council and institution in the criminal justice system.